Retinopathy of prematurity in preterm babies in a local medical college and hospital - Mishra, Shantisena; Saji, Anjali; Behera, Saiprasanna; Mohanty, Sridhar (International Journal of Research in Medical Sciences, 2020)
Background: Retinopathy of prematurity is a multifactorial vasoproliferative retinal disease that increases in incidence with decreasing gestational age and is one of the leading causes of preventable childhood blindness in India. Advances in neonatology have led to dramatic increase in survival of preterm neonates and in turn, to the risk of developing ROP. Since most of the risk factors associated with ROP mentioned above arise in the neonatal intensive care unit (NICU) itself and most of them are avoidable, cautious monitoring of the risk factors, early screening, follow up and surgical intervention have been shown to reduce the incidence and improve the outcome of ROP. Methods: This was a prospective observational study conducted for a period of 2 years. A total of 151 infants admitted in NICU /SNCU who satisfied the inclusion criteria were enrolled in this study. Initial and follow up screening was conducted in three phases the results were documented in proforma after ethical clearance. Results: Comparison of risk factors between eyes with and without ROP was done using Chi-square test. A p-value of<0.05 was considered to be statistically significant. Incidence of ROP in centre is found to be 33.8%. Among maternal risk factors, multiple gestation and PROM/PPROM is found to be significant in the development of ROP from this study. However, mode of delivery and gestational hypertension, were found to be not significant in ROP. Among neonatal risk factors, low birth weight, lower gestational age, prolonged oxygen exposure, blood transfusion, mechanical ventilation, sepsis, phototherapy was found to be significant in this study. Conclusions: ROP, being an emerging cause for potentially blinding visual disability, needs to be diagnosed early. Due to the advancements in neonatology and better survival of preterm babies, timely screening, regular follow up, early detection and intervention is mandatory. A multidisciplinary approach is required in diagnosis and treatment of the disease. Proper counselling and motivation for parents of preterm and low birth weight babies for regular follow up is also essential.